Hearing and Balance Problems in a Chiari-1 Malformation Associated with Communicating Hydrocephalus - A Case Report - Pavan K; Sabarish A (Journal of Clinical and Biomedical Sciences)
Chiari malformation is characterized by an anatomical alteration at the base of the skull, cerebellar herniation, or brainstem herniation via the magnum foramen and up to the cervical spinal canal. It is categorized into five subtypes from type 0 to type IV. The effect of Chiari malformation is reported on the auditory as well as vestibular system due to the nature of the condition. A case of the 36-year-old female came with the complaint of reduced hearing sensitivity and ringing sensation in both ears along with episodes of vertigo, imbalance while walking, and headache and was diagnosed with bilateral cerebellar tonsillar herniation with mild communicating hydrocephalus. Detailed audiological evaluation revealed normal middle ear functioning in both ears, hearing sensitivity within normal limits in the right ear, and severe- profound hearing loss in the left ear, which correlated well with Auditory brainstem response testing. Tinnitus handicap evaluation revealed that catastrophic form of tinnitus and dizziness handicap evaluation revealed a severe form of dizziness. subjective vestibular evaluation revealed nystagmus and instability while testing indicative of vestibular impairment of central origin. The present case report supports the evidence-based practice and the outcomes of a complete audiological evaluation and subjective vestibular evaluation in an adult female with Chiari-1 malformation and communicating hydrocephalus are highlighted in this case report. Hearing loss and balance difficulties can be progressive, thus audiological and vestibular evaluations are vital to understanding pathophysiology, seeking the appropriate therapeutic approach, and enhancing the overall quality of life in these patients.